Controlled spin-torque driven domain wall motion using staggered magnetic wires - H. Mohammed (2020)
Domain wall (DW) memory devices such as racetrack memory offer an alternative to the hard disk drive in achieving high capacity storage. In DW memory, the control of domain wall positions and their motion using spin-transfer torque is an important challenge. In this Letter, we demonstrate controlled domain wall motion using spin-transfer torque in staggered wires. The devices, fabricated using electron-beam and laser lithography, were tested using magneto-optical Kerr microscopy and electrical transport measurements. The depinning current is found to depend on the device dimensions of the staggering wires. Thus, the proposed staggering configuration can be utilized to fine-tune the properties of DW devices for memory applications.